Design and implement of IPTV content repository based on graph database - Xin CAI; Yilong RUAN; Yirong SHI (Dianxin kexue)
Plenty of program content information in the telecom operators IPTV platform can be used to build knowledge base. The traditional way of using relational database to format conversion and storage of knowledge has limitation in the model structure complexity and query visualization and efficiency. Graph database can be used to construct IPTV content knowledge based on the basis of a new graph model. Through the research and comparison, the idea and method of storing and querying the IPTV content repository based on graph database were proposed, and the actual data of a telecom company was used for the scene verification.